PENGUJIAN AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL BUNGA KERSEN (Muntingia calabura L.) MENGGUNAKAN METODE FRAP - Kaisupy, Siti Sumayya; Maryam, St; Tahir, Masdiana (Makassar Pharmaceutical Science Journal (MPSJ), 2025)
Kersen Flower (Muntingia calabura L.) contains several chemical compounds, including flavonoids, tannins, triterpene, saponins and polyphenols that play a role in antioxidant activity. This study aims to determine the antioxidant activity and determine the antioxidant activity value of ethanol extract Muntingia Flower (Muntingia calabura L.) using FRAP (Ferry Reducing Antioxidant Power) method. Extraction was done using maceration method and measurement was done using UV-Vis spectrophotometry method at wavelength of 715 nm. The comparator used was quercetin. The results showed that the concentration of antioxidant activity Muntingia Flower using FRAP method was 684.209 mgQE/g which showed high activity.